Effect Of Phenol Addition To Transformer Oil Breakdown Voltage - Amelya Indah Pratiwi (Pusat Penelitian dan Pengabdian Kepada Masyarakat, 2020)
The failure of transformer insulation often occurs due to various kinds of things, one of which is failure in the oil isolation caused by the condition of oil that has been dirty or has been contaminated with other particles in the transformer. Phenol is a chemical that can purify or cleanse particles or impurities that are in used transformer oil, so that it can increase the breakdown stress on used insulation oil. Phenol contains acid which can attract particles and impurities in the transformer oil which results in a decrease in the breakdown strength of the insulating oil. The results of testing of used isolation oil by adding phenol as much as 10, 15 and 20 ml showed an increase in the value of breakdown voltage with a distance of 2.5 mm ball inlet electrode. Translucent stresses that meet the SPLN standard 49-1: 1982, that is ≥ 30 kV at intervals of 2.5 mm were obtained by adding 20 ml of phenol to the volume of used 400 ml transformer oil